(untitled) (Revista de Administração, 2012)
This study aimed to verify the existence of predictive relationships among the competencies expressed by bank managers, perceived organizational support, number of hours dedicated by the managers to training activities and the performance of the bank branches where they work. Structured questionnaires were used for primary data collection. The sample consisted of 186 bank branch managers and 77 regional superintendents of the Bank of Brazil in the banking retail segment. It also used secondary data on branch performance regarding six dimensions: financial results, strategy and operations, society, customers, processes and organizational behavior. Standard regression analyses were conducted to test the investigation model. The competencies relating to strategic management and financial management turned out to be predictors of different dimensions of branch performance. Other competencies (process management and socio-environmental management), number of hours dedicated to training and managers' perceptions of the company's performance management practices (a dimension of organizational support) appeared to have more modest effects. Once the effects of the control variables had been isolated, the percentage of variance explained by these predictors ranged from 2.2% to 6.8%. Regarding branch performance, the lowest percentage of explanation came from the customer perspective, whereas the greatest variance was explained by the financial results, strategy and operations perspectives. The end of the article discusses the implications of the results and offers practical recommendations.